Penggunaan tepung karkas kijing Taiwan (Anodonta woodiana) dan karkas kerang mutiara (Pinctada margaritifera) dalam formulasi pakan bagi pertumbuhan benih ikan nila (Oreochromis niloticus) di kolam budidaya - Sedu, Aprini L.; Lumenta, Cyska; Kalesaran, Ockstan J. J.; Sinjal, Julius H. (Universitas Sam Ratulangi, 2020)
This study aimed to determine the effectiveness of feed formulated from Taiwan gravestone carcass flour and pearl mussel carcass flour for the growth of tilapia (Oreochromis niloticus). Tilapia used in this study amounted to 300 individuals with an average weight of 2 g per individual. Â Five treatments were used with 3 replications including treatment A (0% Anodonta woodiana carcass flour, 5% Pinctada margaritifera carcass flour and 40% fish meal), B (10% A. woodiana carcass, 5% P. margaritifera carcass flour and 30% fish meal), C (20% A. woodiana, 5% P. margaritifera carcass flour and 20% fish meal), D (30% A. woodiana, 5% P. margaritifera carcass flour and 10% fish meal), E (40% A. woodiana, 5% P. margaritifera carcass flour and 0% fish meal). The data was analysed using analysis of variance in a completely randomized design (CRD). The fish was reared in a net of 15 units with a size of L x W x H = 50 x 50 x 56 cm. The variables analyzed in this study were absolute growth, daily growth, feed efficiency, feed conversion value and survival. The collection of growth data was carried out by measuring the weight of fish at the beginning and end of the study using a digital scale with a precision level of 0.01 g. The results of the research through Duncan's tests showed that the treatments of A, B and E were the same in spurring the absolute, relative, and daily growth. The same result was observedin the value of feed efficiency and feed conversion, where between treatments A, B and E had similar effect in utilizing the feed during the experiment.